Asymmetric reductive amination by a wild-type amine dehydrogenase from the thermophilic bacteria Petrotoga mobilis12. Issue 20 (17th August 2016) - Mayol, Ombeline; David, Sylvain; Darii, Ekaterina; Debard, Adrien; Mariage, Aline; Pellouin, Virginie; Petit, Jean-Louis; Salanoubat, Marcel; de Berardinis, Véronique; Zaparucha, Anne; Vergne-Vaxelaire, Carine
Abstract : Biocatalytic potential of a new wild-type amine dehydrogenase used in an enzyme-catalyzed synthesis of an enantiomerically pure primary amine. Abstract : The biocatalytic reductive amination of ketone to chiral amine is one of the most challenging reactions. Using a genome-mining approach, we found proteins catalyzing the reductive amination of ketones without a carboxylic function in the α or β position. The synthesis of (4 S )-4-aminopentanoic acid (ee ≥99.5%) was achieved with the thermoactive amine dehydrogenase (AmDH) AmDH4 from Petrotoga mobilis in 88% yield. The high stability and substrate tolerance make AmDH4 a very good starting point for further discovery of reductive amination biocatalysts with an enlarged substrate range. This is the first report of wild-type enzymes with related genes having proper NAD(P)H–AmDH activity.